Awareness About Anti-Smoking Related Laws and Legislation Among General Population in Slums of Delhi, India. Issue 5 (5th May 2017) - Sharma, Nandini; Anand, Tanu; Grover, Shekhar; Kumar, Arun; Singh, Mongjam M; Ingle, Gopal K
Abstract: Introduction: Almost 40% of Delhi's population lives in slums and is vulnerable to tobacco use. It is therefore important to assess their opinion and ensure compliance to antismoking legislation. The present study was undertaken to assess the awareness of the general public residing in slums in Delhi regarding the smoke-free initiative of 2009, 3 years after intensive implementation. Methods: It was a cross-sectional study conducted among participants selected by cluster sampling from the slums in six districts of Delhi using a pretested semistructured questionnaire. A total of 708 slum dwellers were interviewed. Results: Out of the total, only 16.1% ( n = 114) of the participants had heard of The Cigarettes and Other Tobacco Products (Prohibition of Advertisement and Regulation of Trade and Commerce, Production, Supply and Distribution) Act, 2003 (COTPA), though, they were aware about some of the provisions of the COTPA. Majority ( n = 529; 74.7%) perceived the smoke-free zones as the places where smoking forms of tobacco are banned. Regarding the awareness about the places designated as smoke-free zones, 82.1% ( n = 581) of the respondents named educational institutions. About 61% of the people interviewed reported to have seen people smoking at public places on the day of interview while only 21.5% reported to have seen any one getting punished for smoking. Conclusions: Awareness about COTPA was low. The study respondents perceived that no action was being taken against persons acting in violation of the law. Thus, there is a need for stricter implementation of COTPA and increased spreading of awareness among the general public. Implications: While awareness about antismoking legislation among general population (particularly slums) has been studied world over, this has not been the case in India. The study depicts opinion of one of the susceptible populations regarding tobacco control legislation, which has hitherto not been studied in the Indian context. This study has an important implication as it highlights the need for stringent enforcement of antismoking legislation for tobacco control.